The Influence of Native Deer on Forest Fauna—A Systematic Map - Sebastian Schwegmann; Manisha Bhardwaj; Ilse Storch (Ecology and Evolution)
ABSTRACT Deer are the most abundant large herbivores in temperate and boreal forests across the Northern Hemisphere. They are ecosystem engineers known to alter understory vegetation and future tree species composition by selective browsing. Also, deer have strong impacts on faunistic groups, often mediated by vegetation. The ongoing loss of faunal biodiversity in forests worldwide can be exacerbated by high deer population densities. Adapted deer management for the purpose of forest biodiversity conservation requires a holistic understanding of deer–fauna relationships. In this systematic map, we examine the existing literature assessing the effects of deer on faunal communities in boreal and temperate forests. Our aim is to synthesize currently described trends and identify research gaps for our understanding of deer as biotic drivers of forest communities. We reviewed 64 studies on how the abundance, species richness, or diversity of faunal taxa responded to different levels of deer abundance or density in forest ecosystems across the Northern Hemisphere. In total, we found almost 400 individual reported effects of nine native deer species on forest‐dwelling faunal communities. However, our systematic map reveals that comprehensive synthesis of the current literature remains a challenge. Published studies often do not report contextual data essential for comparison and meta‐analysis, for example, deer density, forest management, and predation pressure. Moreover, the methodological approaches of the included studies often only account for potential linear effects of deer on fauna, likely oversimplifying the complexity of direct and indirect effects that deer can have on their ecosystem. We recommend that multi‐level enclosure experiments be applied to assess the impact on faunal taxa. This approach combines robust causal inference with the potential straightforward comparison and replication between deer species, forest types, and system productivity, which will facilitate the utilization of the results in future research and management.